Supercooling and Freezing of HNO3/H2O Aerosols - Dickens, Dustin (University of Waterloo, 2000)
The freezing kinetics of binary nitric acid/water aerosols is of fundamental importance to the modelling of polar stratospheric clouds and the role they in ozone depletion over the Arctic/Antarctic regions. Cirrus clouds are also often composed of nitric acid solutions, hence an understanding of freezing process in these aerosols also aids in modelling the earth's radiation budget and global warming. This thesis explores the kinetic phase diagram of nitric acid/water aerosols with sizes ranging between 0. 2 and 1. 5 mm in radius and concentrations ranging between pure water and 0. 45 mole fraction HNO3. Although the kinetic phase diagram has now been studied between 0. 46 mole fraction HNO3 and pure water, more data is needed in the region between 0. 18 and 0. 25 mole fraction HNO3 to confirm the results reported. The project described in this thesis are a continuation of a project begun by Allan Bertram. The measurements involving aerosols with compositions greater than 0. 25 mole fraction HNO3 were carried out as part of Allan Bertram's Ph. D. thesis (see ref. 20) These data were later examined using a more comprehensive data analysis method (as presented in this thesis) in an effort to obtain a more complete understanding of this system.